ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEMERIKSA PAJAK : ANALYSIS OF FACTORS AFFECTING THE PERFORMANCE OF TAX AUDITORS - Putri Sinaga, Nia Paramitha; Nasrizal, Nasrizal; Adhitya Agri Putra (Universitas Riau, 2022)
This study aims to examine: the effect of professional ethics, competence, work experience, dan professionalism on tax auditor performance. The population used in this study was well from employees who have positions as tax auditors at Tax Office in Pekanbaru City. The sampling technique used in this study is saturated sampling. Saturated sampling is taken because all members of the population are used as samples. This study used primary data by distributing questionnaires. Data analysis in this study used the Partial Least Square (PLS) with the aid of SmartPLS computer software version 3. The result of this study indicated that: (1) professional ethics positively and significantly affect tax auditor performance, (2) competence positively and significantly effect on tax auditor performance, (3) work experience positively and significantly effect on tax auditor performance, (4) professionalism positively and significantly effect on tax auditor performance